2022
DOI: 10.2807/1560-7917.es.2022.27.31.2200561
|View full text |Cite
|
Sign up to set email alerts
|

Functional immunity against SARS-CoV-2 in the general population after a booster campaign and the Delta and Omicron waves, Switzerland, March 2022

Abstract: Functional immunity (defined here as serum neutralising capacity) critically contributes to conferring protection against SARS-CoV-2 infection and severe COVID-19. This cross-sectional analysis of a prospective, population-based cohort study included 1,894 randomly-selected 16 to 99-year-old participants from two Swiss cantons in March 2022. Of these, 97.6% (95% CI: 96.8–98.2%) had anti-spike IgG antibodies, and neutralising capacity was respectively observed for 94%, 92% and 88% against wild-type SARS-CoV-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
3
20
1
Order By: Relevance
“…There are a variety of neutralization assays that have been described to be able to measure functional antibody neutralization against wild-type as well as variant SARS-CoV-2 that involve binding proxy assays ( 24 27 ), pseudovirus, or VLP neutralization ( 7 , 25 , 26 ) as well as SARS-CoV-2 culture-based neutralization ( 26 , 28 ). Not all methods compare wild-type or variant SARS-CoV-2 neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of neutralization assays that have been described to be able to measure functional antibody neutralization against wild-type as well as variant SARS-CoV-2 that involve binding proxy assays ( 24 27 ), pseudovirus, or VLP neutralization ( 7 , 25 , 26 ) as well as SARS-CoV-2 culture-based neutralization ( 26 , 28 ). Not all methods compare wild-type or variant SARS-CoV-2 neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…The current study includes results from phases five and six, for which assessments were conducted between 1 March and 1 April 2022 and 30 May and 11 July, respectively. 12…”
Section: Methodsmentioning
confidence: 99%
“…The current study includes results from phases five and six, for which assessments were conducted between 1 March and 1 April 2022 and 30 May and 11 July, respectively. 12 In phase five, we randomly selected individuals from the general population in southern (canton of Ticino) and north-eastern (canton of Zurich) Switzerland, who were assessed again in phase six. For cross-sectional analyses in phase six, we supplemented the southern and eastern Switzerland sample with a random sample from the general population in western Switzerland (canton of Vaud).…”
Section: Study Design Sampling and Participantsmentioning
confidence: 99%
“…They were followed-up at two and four months after baseline to elicit data on PCC-related symptoms, current health status, new infections, and vaccinations. 5,21,23 For this study, we included all participants who, either at baseline or during follow-up, reported having last been infected by SARS-CoV-2 during the timeframes of predominance of the Delta and Omicron variants (see definition below), and who completed the baseline or either of the follow-up assessments approximately six months after the most recent reported infection (five to seven months allowed; Supplementary Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…21,22 For this study, we leveraged data from the fifth phase of Corona Immunitas and associated follow-up from the cantons of Zurich (largest canton in German-speaking north-eastern Switzerland with around 18% of the Swiss population), and Ticino (Italian-speaking part with about 4% of Swiss population), Switzerland, including 1844 participants, for which baseline assessments took place between Mar 1-31, 2022. 23 The study was registered (https://doi.org/10.1186/ISRCTN18181860) and approved by the ethics committees of the cantons of Zurich (BASEC 2020-01247) and Ticino (BASEC 2020-01514). All participants provided informed consent prior to participation.…”
Section: Study Design and Participantsmentioning
confidence: 99%